A Review on Advances in Extraction Technologies, Analytical Characterization, and Various Applications of Astaxanthin Derived from Seafood Waste - Sedyaaw, Panchakarla; Kalluri, Sravani; Meshre, Supriya D.; Bhatkar, Varsha R.; Bhaladhare, Darwin Ratnaghosh; Kamble, Pranali Arun; Kawade, Sanket Sunil; Janbandhu, Shubham; Alam, Md. Shadab (International Journal of Bio-resource and Stress Management, 2025)
Astaxanthin, a red-orange carotenoid (3,3′-dihydroxy-β, β-carotene-4,4′-dione) with potent antioxidant, anti-inflammatory, and therapeutic effects, is a valuable bioactive compound sustainably extracted from discarded shrimp and crab shells. As seafood industries grow, these by-products pose environmental challenges yet represent an untapped astaxanthin source competing traditional microalgal origins. This review emphasizes astaxanthin’s abundance in crustacean shells and the critical role of handling and processing in preserving yield and integrity. Traditionally sourced from Haematococcus pluvialis, its commercial use is limited by high cultivation costs. Recently, shrimp and crab shells-common seafood waste-have emerged as sustainable, cost-effective alternatives. The review rigorously discusses extraction methods including ethanol-based, ultrasonic, supercritical CO2, enzymatic, and emerging green solvents, evaluating yields, sustainability, cost, and scalability. Ethanol-based ultrasound-assisted extraction achieved efficient, eco-friendly yields up to 239.96 µg g-1 in Procambarus clarkii shells. Silica gel chromatography enhanced purity to 85.1%, enabling use in functional foods, cosmetics, and pharmaceuticals. Purification techniques employing advanced chromatographic and spectrophotometric assays convert crude extracts into pharmaceutical-grade astaxanthin. Applications span food systems-emulsions, microcapsules, antioxidant films-and cosmetics featuring liposomes, nanoemulsions, and cyclodextrins to optimize stability and bioavailability. Each technology balances bioactivity, shelf-life, and safety compliance. The review concludes by highlighting the imperative for safe, effective, and economically viable astaxanthin recovery from seafood waste, aiming to advance sustainable, high-value compound production for food, pharmaceutical, and cosmetic sectors while mitigating environmental impact.